2011
DOI: 10.1016/j.chemosphere.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of various laccases induced by anthracene and contribution to its degradation in a Mediterranean coastal pine litter

Abstract: Mediterranean coastal ecosystems are known to be highly subject to natural and anthropic environmental stress. In this study, we examine the effects of anthracene as a common pollutant on the total microbial communities from a Pinus halepensis litter of a typical Mediterranean coastal site (Les Calanques, Marseille). The main objective was to identify the microbial factors leading the resilience of this ecosystem. Two questions were addressed: (i) how lignin-degrading enzymes (Laccase, Lignin-peroxidase and Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Enzyme extracts were further subjected to gel electrophoresis according to Qasemian et al (2011) in order to compare the phenoloxidase bands, as revealed by activity, under each treatment.…”
Section: Extracellular Enzyme Activities (Eea)mentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme extracts were further subjected to gel electrophoresis according to Qasemian et al (2011) in order to compare the phenoloxidase bands, as revealed by activity, under each treatment.…”
Section: Extracellular Enzyme Activities (Eea)mentioning
confidence: 99%
“…While the ways in which microorganisms mineralize organic contaminants have been extensively documented in studies on bioremediation technologies (Gianfreda and Rao, 2004;Novotný et al, 2004;D'Annibale et al, 2006;Wu et al, 2008), little is known about how far autochthonous microbial communities can withstand PAHs and whether they may be involved in degrading theses pollutants. In our previous study, we showed that anthracene, a model PAH, artificially added in laboratory experiments (Qasemian et al, 2011(Qasemian et al, , 2012 has no toxic effects on microbial activities expressed by whole microbial communities in Pinus halepensis litter from a coastal Mediterranean site. It therefore appeared useful to compare these results obtained from litters in coastal environments with the responses of microbial communities from inland areas.…”
Section: Introductionmentioning
confidence: 95%
“…In a previous study, we tested the effects of various metal and halide salts on the laccases from Marasmius quercophilus and we found that certain laccase isoforms were actually strongly inhibited by chloride ions (Farnet et al 2009). On the other hand, we found high laccase activities in a Pinus halepensis litter from Mediterranean coastal areas subjected to high osmotic pressure (Qasemian et al 2011). Furthermore, coastal areas are known to be highly urbanized and thus chronically subjected to anthropic pollutants such as PAHs.…”
Section: Introductionmentioning
confidence: 72%
“…They also play an important role in aromatic pollutant transformation. Previous studies have shown that fungal activities considerably enhanced anthracene transformation in soil microcosms (Steffen et al, 2007) and in litter microcosms (Qasemian et al, 2011). Moreover, recent studies on emerging pharmaceutical pollutants have reported that carbamazepine can also be transformed by laccases (Jelic et al, 2012;RodriguezeRodriguez et al, 2010;Zhang and Geißen, 2012).…”
Section: Resultsmentioning
confidence: 96%